“CROPWAT 8.0 in Irrigation Management: A Review of Methods and Applications” (International Journal of Agricultural Extension and Education, 2025)
When it comes to effective farming, irrigation management is an important factor due to the increasing climate changes and scarcity of water. The Food and Agriculture Organization developed CROPWAT 8.0, a decision support tool which enables the user to calculate the needs of a crop and set up the best timing for the irrigation. This review paper describes the methods and the workings of CROPWAT 8.0 in regard to irrigation scheduling, giving special attention to innovations and developments registered after its launch. Important issues include the combination of CROPWAT with remote sensing and climate models, regional studies showing its practical usefulness and its contribution in the development of water management strategies Researchers identify crucial hurdles like data scarcity and necessity for real-time apps they discuss potential future paths. Recent research synthesis underscores CROPWAT 8.0’s crucial impact on water use efficiency globally through myriad sustainable agricultural practices.
Keywords: cropwat8.0; irrigation scheduling; water